Socioeconomic and Demographic Factors for Spousal Resemblance in Obesity Status and Habitual Physical Activity in the United States - Hsin-Jen Chen; Yinghui Liu; Youfa Wang (Hindawi Limited, 2014)
Studies suggested that the married population has an increased risk of obesity and assimilation between spouses' body weight. We examined what factors may affect married spouses' resemblance in weight status and habitual physical activity (HPA) and the association of obesity/HPA with spouses' sociodemoeconomic characteristics and lifestyles. Medical Expenditure Panel Survey data of 11,403 adult married couples in the US during years 2006-2008 were used. Absolute-scale difference and relative-scale resemblance indices (correlation and kappa coefficients) in body mass index (BMI) and HPA were estimated by couples' socioeconomic and demographic characteristics. We found that spousal difference in BMI was smaller for couples with a lower household income, for who were both unemployed, and for older spouses. Correlation coefficient between spouses' BMI was 0.24, differing by race/ethnicity and family size. Kappa coefficient for weight status (obesity: BMI ≥ 30, overweight: 30 > BMI ≥ 25) was 0.11 and 0.35 for HPA. Never-working women's husbands had lower odds of obesity than employed women's husbands (OR = 0.69 (95% CI = 0.53-0.89)). Men's unemployment status was associated with wives' greater odds of obesity (OR = 1.31 (95% CI = 1.01-1.71)). HPA was associated with men's employment status and income level, but not with women's. The population representative survey showed that spousal resemblance in weight status and HPA varied with socioeconomic and demographic factors.